Endophytic Bacteria as Biocontrol Agents of Tomato Bacterial Wilt Disease - Arika Purnawati (Journal of Tropical Life Science, 2014)
Ralstonia solanacearum is one important pathogen on tomato because it caused wilt disease that can loss yield until 100%. The object of these experiment are to select of endophytic bacteria that was isolated from healthy tomato stems, root and to investigate of them as biocontrol agents for tomato bacterial wilt disease. There are 10 isolates successfully isolated and two isolates are Ps1 and Ps8 can inhibit of R. solanacearum. The result show the two isolates are Ps1 and Ps8 significantly suppress disease incidence until 8.07-9.19%.